Quantitative anatomy of the fused ossification center of the occipital squama in the human fetus - Grzonkowska, Magdalena (PLoS One, 2021)
CT-based quantitative analysis of any ossification center in the cranium has not previously been carried out due to the limited availability of human fetal material. Detailed morphometric data on the development of ossification centers in the human fetus may be useful in the early detection of congenital defects. Ossification disorders in the cranium are associated with either a delayed development of ossification centers or their mineralization. These aberrations may result in the formation of accessory skull bones that differ in shape and size, and the incidence of which may be misdiagnosed as, e.g., skull fractures. The study material comprised 37 human fetuses of both sexes (16♂, 21♀) aged 18–30 weeks. Using CT, digital image analysis software, 3D reconstruction and statistical methods, the linear, planar and spatial dimensions of the occipital squama ossification center were measured. The morphometric characteristics of the fused ossification center of the occipital squama show no right—left differences. In relation to gestational age, the ossification center of the occipital squama grows linearly in its right and left vertical diameters, logarithmically in its transverse diameters of both the interparietal and supraoccipital parts and projection surface area, and according to a quadratic function in its volume. The obtained numerical findings of the occipital squama ossification center may be considered age-specific references of relevance in both the estimation of gestational age and the diagnostic process of congenital defects.